VD_FINDINFO Pron / 2013 / 125 vom 15. Mai 2013 - VD Tribunal cantonal (2013)
DÉCISION D'IRRECEVABILITÉ, COMPÉTENCE RATIONE MATERIAE | 74 LOJV, 96g LOJV, 5 CPC (CH), 59 CPC (CH), 60 CPC (CH), 8 CPC (CH)